1978
DOI: 10.1007/bf00383640
|View full text |Cite
|
Sign up to set email alerts
|

ersuchungen zur biomechanik des oberen sprunggelenks bei verk�rzungen des au�enkn�chels

Abstract: Shortening of the distal fibula after malleolar fracture is accompanied with important alterations of the biomechanics and the compressive forces of the ankle joint. The relationship between the extent of shortening, the degree of valgus position of the talus and the reduction of the joint surfaces is described on the basis of experimental investigations. The importance of these circumstances for treatment of malleolar fractures is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Even a displacement of as little as 1 mm will change the mobility of the talus and fibula, and the distribution of load in the talofibular and talotibial articulations [1,5,7,8,11,12,13,15]. Recent experimental studies on cadaveric ankles showed that 30° of lateral rotation deformity decreases the tibiotalar contact area by 30 to 50% [2,12], and this may lead to abnormal stress on the cartilage and underlying bone [19].…”
Section: Discussionmentioning
confidence: 99%
“…Even a displacement of as little as 1 mm will change the mobility of the talus and fibula, and the distribution of load in the talofibular and talotibial articulations [1,5,7,8,11,12,13,15]. Recent experimental studies on cadaveric ankles showed that 30° of lateral rotation deformity decreases the tibiotalar contact area by 30 to 50% [2,12], and this may lead to abnormal stress on the cartilage and underlying bone [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the fibula helps maintain stability during weightbearing. 8 Following an ankle fracture, the fibular fracture deformity is usually shortening and external rotation. This shortening permits lateral shift of the talus with persistent instability and valgus tilt.…”
Section: Discussionmentioning
confidence: 99%
“…Even displacement of one millimeter will change the mobility of the talus and fibula and the distribution of the load in the talofibular and talotibial articulations. 2,46,8–10,12,14 Objectively this shortening can be measured by comparing talocrural angles of the affected side with the normal side. The talocrural angle, as described by Sarkisian et al, 15 is the angle between a perpendicular line to the tibial plafond and a line drawn between the tips of the malleoli (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Diese Hypothese ("Leitstabtheorie") wurde durch biomechanische Untersuchungen von Martinek [16] unterstützt, der nach einer Wadenbeinverkür-zung ab 4 mm einen signifikanten Anstieg der Gelenkfehlbelastung feststellte. Yoshimine [31] bestätigte dies, konnte aber zusätzlich für eine experimentelle Außenrotationsfehlstellung der distalen Fibula von 20°keine gravierenden biomechanischen Veränderungen im OSG feststellen.…”
Section: Rotationunclassified